metaFlye: scalable long-read metagenome assembly using repeat graphs - Kolmogorov, Mikhail; Bickhart, Derek M.; Behsaz, Bahar; Gurevich, Alexey; Rayko, Mikhail; Shin, Sung Bong; Kuhn, Kristen; Yuan, Jeffrey; Polevikov, Evgeny; Smith, Timothy P. L.; Pevzner, Pavel A. (Nature methods, 2020)
Long-read sequencing technologies have substantially improved the assemblies of many isolate bacterial genomes as compared to fragmented short-read assemblies. However, assembling complex metagenomic datasets remains difficult even for state-of-the-art long-read assemblers. Here we present metaFlye, which addresses important long-read metagenomic assembly challenges, such as uneven bacterial composition and intra-species heterogeneity. First, we benchmarked metaFlye using simulated and mock bacterial communities and show that it consistently produces assemblies with better completeness and contiguity than state-of-the-art long-read assemblers. Second, we performed long-read sequencing of the sheep microbiome and applied metaFlye to reconstruct 63 complete or nearly complete bacterial genomes within single contigs. Finally, we show that long-read assembly of human microbiomes enables the discovery of full-length biosynthetic gene clusters that encode biomedically important natural products. Long-read metagenomics offers a valuable approach for profiling bacterial communities. This work presents a long-read assembler, metaFlye, that specifically addresses the challenges of assembling metagenomes.